States as Actors in International Agro-Investments - Martin Keulertz; Eckart Woertz (Revue Internationale de Politique de Développement)
Since the global food crisis of 2008 states have encouraged international agro-investments by their respective private sectors or have undertaken them directly via state-owned companies and sovereign wealth funds. This chapter analyses the crucial role played by national governments with the help of three case studies: the Gulf countries, China, and potential host countries. It thus shows the varying constraints experienced by these three cases and the strategies pursued to overcome them. States in the Gulf are heavily dependent on food imports and are concerned that export restrictions could undermine their food security. For the same reason, China has pursued a strategy of grain self-sufficiency, which is now being modified in the light of recent changes to diet and rises in demand. Governments in potential host countries and regions, like South-East Asia, Russia, and Brazil, on the other hand, have sought to keep their agricultural export industries national, maximise their revenue streams, and leverage them for geopolitical purposes. While much of the literature has focused on ‘land grabbing’ by foreign states in developing countries, this chapter offers a different perspective by placing the interests of states into the context of twenty-first century food politics. It concludes that: the focus of investments has been on value chains downstream rather than on farmland in the upstream sector; that ‘security mercantilism’ is far more complex than the land acquisition processes themselves; and that emerging economies in Asia seek to challenge the Western world in its hegemony over food production and virtual water trade.